Systemic approach to Smart Urban Transformations Of Cities Case of Muscat- Oman - Sallam, Islam; Abdelghani , Montasser (International Journal of Membrane Science and Technology, 2023)
A smart city concept ensures sustainable development and addresses urgent urban, social, economic, and environmental concerns. Smart cities have significant potential for improving the economy and living conditions of cities and their residents; however, this potential has yet to be fully realized in many countries. Given its escalating urban challenges, the current international smart-city frameworks and models are insufficient to enable developing cities, such as Muscat city of Oman, to implement the smart-city concepts successfully. Literature review and previous studies indicate a lack of studies on systematic methodologies and standards to manage, initiate, and process the urban transformation towards smart cities in developing countries. It is due to a lack of knowledge regarding the unique characteristics of methodological frameworks for smart transformation tailored to each country's social, economic, and political circumstances. This paper aims to present an integrated methodological framework for urban transformation in the context of the social, economic, and governmental factors that affect each country's approach to smart and sustainable cities. The study depended on a qualitative and critical analysis of a selective body of literature and studies. The study presents a framework that differs from previous frameworks presented in the context of developing countries as it includes: the stages of preparation, groundwork, and setting of the basis for the city, as well as the importance of these stages in building the bridges between reality and hope; KPIs at different stages allow comparison of city performance before and after based on a smart urban transformation model, a smart city planning strategy, and an Omani case study focused on the smart cities concept. Finally, the study ends by presenting a proposed model, “CLEVER”, that is assumed to be an effective approach to the smart transformation of cities in developing countries such as Muscat-Oman.